Proactive strategies to optimize engagement of Black, Hispanic/Latinx, transgender, and nonbinary individuals in a trial of a novel agent for HIV pre-exposure prophylaxis (PrEP) - Cespedes, Michelle; Das, Moupali; Hojilla, J. Carlo; Blumenthal, Jill; Mounzer, Karam; Ramgopal, Moti; Hodge, Theo; Torres, Thiago S.; Peterson, Charles; Shibase, Senzokuhle; Elliott, Ayana; Demidont, A. C.; et al. (PLOS ONE, 2022)
Introduction Black and Hispanic/Latinx cisgender men who have sex with men (MSM), transgender women, transgender men, and gender nonbinary (TGNB) individuals have been historically underrepresented in HIV pre-exposure prophylaxis (PrEP) clinical trials. There is an urgent need for ongoing engagement with communities that have been the most impacted by HIV and diverse representation in clinical trials. Here we describe strategic approaches undertaken in the PURPOSE 2 trial to optimize engagement of underrepresented individuals. Methods and results PURPOSE 2 is an ongoing Phase 3 trial evaluating the safety and efficacy of lenacapavir as PrEP in cisgender MSM and TGNB individuals. In PURPOSE 2, we used a multipronged approach aimed at enriching participation of underrepresented individuals. We conducted a review to identify evidence-informed recommendations from literature, engaged with stakeholders, and established the Global Community Advisory and Accountability Group (GCAG) to represent the needs of the community. Insights from stakeholders and GCAG members resulted in an expansion of the study population to include transgender men, gender nonbinary persons, and adolescents, and evaluation of population-specific outcomes. Feedback from stakeholders and GCAG members also informed investigator and site selection; these were selected based on prior experience working with persons from diverse racial, ethnic and gender identities, and estimates of local HIV incidence. Site selection was also expanded to include community-based clinics with services tailored towards Black, Hispanic/Latinx, and TGNB populations. We established a study-wide recruitment goal of 50% Black MSM and 20% Hispanic/Latinx MSM in US sites and 20% transgender women globally. Site-specific recruitment goals were also developed based on local demographics and HIV incidence. Mandatory trainings included Good Participatory Practice guidelines, gender inclusivity, and antiracism. Conclusion While further work is needed to achieve equitable representation, the strategies we describe may serve as a framework for future clinical trials. Trial registration Clinical Trial Number: NCT04925752.